2013
DOI: 10.1002/ange.201303931
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis and Antimalarial Activity of All Four Mefloquine Stereoisomers Using a Highly Enantioselective Catalytic Borylative Alkene Isomerization

Abstract: Plus und Minus von Mefloquin: Die Optimierung einer hoch enantioselektiven Methode mit katalytischer borylierender Isomerisierung und Aldehyd‐Allylborierung für die stereoselektive Synthese von Mefloquin macht alle vier Stereoisomere des Antimalariawirkstoffs (siehe Schema) und seiner Analoga zugänglich. Die absolute Konfiguration dieser Verbindungen wurde erstmals über eine chemische Synthese bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…In conclusion, we have reported a five-step total synthesis of all four stereoisomers of mefloquine. In contrast to previous syntheses, [15] excepting the most recent synthesis, [16] we have obtained all four possible stereoisomers of mefloquine, including (À)-(11R,12S)-erythro-mefloquine 1 a and (+)-(11S,12R)-erythro-mefloquine ent-1 a. This constitutes a synthetic approach that synthesises all four stereoisomers of mefloquine correctly and supports the recent enantioselective synthesis [16] according to a different synthetic pathway.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In conclusion, we have reported a five-step total synthesis of all four stereoisomers of mefloquine. In contrast to previous syntheses, [15] excepting the most recent synthesis, [16] we have obtained all four possible stereoisomers of mefloquine, including (À)-(11R,12S)-erythro-mefloquine 1 a and (+)-(11S,12R)-erythro-mefloquine ent-1 a. This constitutes a synthetic approach that synthesises all four stereoisomers of mefloquine correctly and supports the recent enantioselective synthesis [16] according to a different synthetic pathway.…”
Section: Resultssupporting
confidence: 83%
“…While preparing this manuscript, Hall and co-workers published the first synthetic approach, which delivered the correct stereochemical outcome. [16]…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the solvent under vacuum and crystallization from Et 2 O gave (11 R ,12 S )‐(−)‐ erythro ‐mefloquine hydrochloride as a white solid; yield: 76 mg (88%). Spectral and rotation data match those reported 29. [α]${{{20\hfill \atop {\rm D}\hfill}}}$ : −33.7 ( c =0.5, MeOH); 1 H NMR (DMSO‐ d 6 , 400 MHz): δ =10.48 (br s, 1 H), 9.04 (d, 1 H, J =8.4 Hz), 8.50 (br s, 1 H), 8.39 (d, 1 H, J =7.2 Hz), 8.10 (s, 1 H), 7.97 (t, 1 H, J =8.0 Hz), 6.85 (d, 1 H, J =4.4 Hz), 6.15 (s, 1 H), 3.30 (m, 1 H), 3.25 (m, 1 H), 2.91 (m, 1 H), 1.66 (m, 4 H), 1.33(m, 2 H); 13 C NMR (DMSO‐ d 6 , 100 MHz): δ =151.8, 147.1 (q, J =34.3 Hz), 143.2, 130.4 (q, J =5.4 Hz), 129.8, 128.8, 127.6 (q, J =29.4 Hz), 126.9, 124.1 (q, J =272 Hz), 121.7 (q, J =280 Hz), 115.8, 67.1, 59.2, 44.6, 22.0, 21.6, 21.3.…”
Section: Methodssupporting
confidence: 84%
“…After submission of this manuscript, Hall reported the stereoselective synthesis and antimalarial activity of all four mefloquine stereoisomers 29. In this elegant work, they validated the absolute configurations of mefloquine stereoisomers for the first time utlizing a chemical method, and demonstrated that the most potent stereoisomer in antimalarial assays is (11 S ,12 S )‐(+)‐ threo ‐mefloquine rather than (11S,12 R )‐(+)‐ erythro ‐mefloquine!…”
Section: Methodsmentioning
confidence: 98%
“…2). 33,34 The resulting chiral pyranyl and piperidyl allylic boronates 3 and 4 can lead to either a-or gregioselectivity in a Suzuki Miyaura cross-coupling with organohalide electrophiles (RX). This regioselectivity is tied to the mechanistic nature of the transmetallation step and whether it occurs with or without allylic rearrangement [22][23][24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%